2011
DOI: 10.1371/journal.pone.0027940
|View full text |Cite
|
Sign up to set email alerts
|

A Contracted DNA Repeat in LHX3 Intron 5 Is Associated with Aberrant Splicing and Pituitary Dwarfism in German Shepherd Dogs

Abstract: Dwarfism in German shepherd dogs is due to combined pituitary hormone deficiency of unknown genetic cause. We localized the recessively inherited defect by a genome wide approach to a region on chromosome 9 with a lod score of 9.8. The region contains LHX3, which codes for a transcription factor essential for pituitary development. Dwarfs have a deletion of one of six 7 bp repeats in intron 5 of LHX3, reducing the intron size to 68 bp. One dwarf was compound heterozygous for the deletion and an insertion of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 48 publications
1
45
1
Order By: Relevance
“…As discussed earlier, pituitary dwarfism in the German Shepherd dog (and related breeds such as the Karelian Bear dog, Saarloos Wolfhound, and Czechoslovakian Wolfdog) is due to a mutation in the LHX3 gene (Voorbij et al, 2011). As discussed earlier, pituitary dwarfism in the German Shepherd dog (and related breeds such as the Karelian Bear dog, Saarloos Wolfhound, and Czechoslovakian Wolfdog) is due to a mutation in the LHX3 gene (Voorbij et al, 2011).…”
Section: Endocrinological Evaluation and Diagnosismentioning
confidence: 86%
See 2 more Smart Citations
“…As discussed earlier, pituitary dwarfism in the German Shepherd dog (and related breeds such as the Karelian Bear dog, Saarloos Wolfhound, and Czechoslovakian Wolfdog) is due to a mutation in the LHX3 gene (Voorbij et al, 2011). As discussed earlier, pituitary dwarfism in the German Shepherd dog (and related breeds such as the Karelian Bear dog, Saarloos Wolfhound, and Czechoslovakian Wolfdog) is due to a mutation in the LHX3 gene (Voorbij et al, 2011).…”
Section: Endocrinological Evaluation and Diagnosismentioning
confidence: 86%
“…2-2 for the differentiation of pituitary cell lineages and the main important transcription factors involved. More recently, the search was successful, and the genetic defect could be located in the LHX3 gene (Voorbij et al, 2011). It was, therefore, reasonable to explore potential defects in those two genes also in the German Shepherd.…”
Section: Non-endocrine Causes Of Growth Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Considering all our results, we conclude that the conservation of the exon 1 terminal sequence in vertebrates reflects a restriction on a splicing requirement rather than on a functional requirement of the encoded amino acid. Characterization of naturally occurring mutations that are uncovered because of an association with disease can render important insights in splicing requirements [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that molecular defects of the LHX3 gene are associated with CPHD . LHX3, a member of the LIM homeodomain protein family of DNA‐binding transcription factors, is an essential regulator of pituitary development .…”
mentioning
confidence: 99%